Time-dependent Effects of High Intensity Interval Training on Oxygen Kinetics in Females - Tahmineh Ajorlu; Abbas Saremi (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Because VO2max doesn't provide any detailed information about aerobic examinations Oxygen Kinetic is used for more accuracy. Long intensive and repetitive exercises with sufficient time lead to increase in aerobic parameters like kinetic absorption of oxygen. Objectives. The purpose of this study was to determine time dependent effects of short-time high intensity interval training (HIIT) on oxygen kinetics in females. Methods. Forty active and healthy students (age: 25.5±5yr) were randomly allocated to one of four groups: H1, which performed one session HIIT (with 120% vo2 max intensity for 1 minutes and 1 minutes active break for 8 times); H2, which performed two session HIIT; H3, which performed four session HIIT; and a control group (CON). Both exercise and control groups performed the incremental test (initially the work load was 50 watts and after every 4 minutes adding 30 watts and 1 minute active break for recovery) on the ergometer bicycle. After 2 days of pretesting, training groups participated in 1, 2 and 4 session HIIT (with 120% of their Vo2max intensity for 1 minutes and 3 minute active breaks for 8 times). Two days after the completion of the exercise protocol, post-test accordingly pretest was used by control and exercise groups. Result was measured by gas analyzer to breath-by breath method. Results. The findings showed that 1 session HIIT had no significant effect on oxygen kinetic factors (Vo2max, oxygen deficit, time constant 1 and 2) (p>0.05). Two sessions HIIT significantly improved some of oxygen kinetic factors (Vo2max, oxygen deficit, time constant 2) (p<0.05), but had not significant effect on time constant 1 (p>0.05). In addition, 4 sessions HIIT, significantly associated with improvement in all of oxygen kinetic factors (Vo2max, oxygen deficit, time constant 1 and 2) (p<0.05). Conclusion. It seems that 4 sessions HIIT is the at least time for improvement of all oxygen kinetic factors.